Blended model of distance learning: Does it effective? - Mamahit, Calvin Johanes (Jurnal Pendidikan Teknologi Kejuruan, 2020)
This study aims to determine whether distance learning is effective to implement. This study compares the blended model of distance learning with traditional learning. What is being compared is student learning outcomes and their perceptions in these two lessons. This research is a quantitative study using a quasi-experimental research design with a time-series model. The population of this research is all 4th-semester students who take Digital Electronics courses. Data collection was carried out in two ways, namely by using several tests for data on learning outcomes and questionnaires for student perception data. Data analysis was made using the t-test for paired samples. The results of the analysis obtained that there are differences in the two samples tested mean and the distance learning blended model has a higher average than traditional learning. This shows that the blended model of distance learning is more effective than traditional learning.